Identification of negative Gram bacteria in diabetes mellitus gangrene at RSUD dr. Soedomo Trenggalek - Hariyanto Hariyanto; Nala Fidarotul Ulya (Medical Laboratory Analysis and Sciences Journal, 2019)
Diabetes mellitus is a metabolic disease due to an increase in blood glucose levels normal. Gangrene diabetes is tissue death due to obstruction of blood vessels that provides nutrients to obstructed tissue and is a form of complications from diabetes mellitus. Pseudomonas aeruginosa is one of the causes of gangrene infection nosocomial opportunistic infections in humans. The purpose of this study was to determine the presence of gram-negative bacteria in the wounds of Gangrene Diabetes Mellitus. This research is a descriptive Non-Analytic, conducted on April 15 to May 21, 2019, in the Microbiology Laboratory of STIKes Hutama Abdi Husada Tulungagung. The study sample was all patients with Gangrene Diabetes Mellitus wound in hospital dr. Soedomo Trenggalek, the sampling technique used was accidental sampling, obtained a sample of 4 Gangrene swabs. The study was conducted by the identification of gram-negative bacterial isolation. The results of the study were 4 samples, 2 were positive for Pseudomonas aeruginosa and 2 samples were positive for Proteus sp. Subsequent research results were analyzed descriptively. The conclusion of this research is that 100% positive gram-negative. The typical characteristics of the Pseudomonas aeruginosa bacteria are obtained on the MCH media (alkaline slope, alkaline base, negative gas, negative H2S) and on the NAS produce greenish-yellow fluorescence, while the typical characteristics of Proteus sp are obtained on the MCH media (alkaline slope, alkaline slope, base negative) acid, positive gas, positive H2S).